Acute Zonal Occult Outer Retinopathy in a Patient Suffering from Epilepsy: Five-Year Follow-Up - Izabella Karska-Basta (MDPI AG, 2021)
We report an unprecedented case of a young patient with epilepsy coexisting with acute zonal occult outer retinopathy (AZOOR), a rare white dot syndrome of unknown etiology, associated with damage to the large zones of the outer retina. Recently, it has been established that epileptic episodes contribute to an inflammatory response both in the brain and the retina. A 13-year-old male patient with epilepsy was referred by a neurologist for an ophthalmologic consultation due to a sudden deterioration of visual acuity in the left eye. The examination, with a key role of multimodal imaging including color fundus photography, fluorescein angiography, indocyanine green angiography (ICGA), fundus autofluorescence (FAF), swept-source optical coherence tomography (SS-OCT) with visual field assessment, and electroretinography indicated AZOOR as the underlying entity. Findings at the first admission included enlargement of the blind spot in visual field examination along a typical trizonal pattern, which was revealed by FAF, ICGA, and SS-OCT in the left eye. The right eye exhibited no abnormalities. Seminal follow-up revealed no changes in best corrected visual acuity, and multimodal imaging findings remain unaltered. Thus, no medical intervention is required. Our case and recent laboratory findings suggest a causative link between epilepsy and retinal disorders, although this issue requires further research.